The praise of nothing though some doe wonder why I write in praise of nothing, in these lamentable daies, when they have read, and will my counsell take, I hope of nothing something they may make. To the tune of, Though I have but a marke a year, &c (Early English Books Online / EEBO, 1635)
eebo-0166